THEORETICAL AND METHODOLOGICAL FRAMEWORK OF SOCIAL GEOGRAPHY AND ITS USE IN THE MILITARY GEOGRAPHY OF UKRAINE - Masliak, P.; Levinskova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article deals with the possibilities of using theoretical and methodological framework of social geography in the process of formation and development of modern military geography. The author has proposed to use different theories, concepts and principles of social and political geography that will promote diversification of military geography.
Keywords: geopolitics, geostrategy, political and geographical location, remotability, determinancy, potentiality